ePAct System (UiTM Pahang Activities System) / Roslan Jamaludin - Jamaludin, Roslan (2006)
This paper discusses the development of Electronic Activities Information System (ePAct). This system has been developed as a web-based application which runs on Windows Operating System. Presently, Microsoft Access is used as the database engine which utilises the relational database model. The system development uses Hyper Text Markup Language (HTML), Active Server Pages (ASP), Customs Style Sheet (CSS), and Structured Query Language (SQL). The system runs on Internet Information Services (//S) as the web server application and Windows 2003 Server as the platform. The information security is enforced by using DBMS database password, user level and session. The system is easy to use and learn. Thus, it proposes to be a master planner of UiTM Pahang activities calendar. The system will be integrated with other applications which are under development.